Building Leadership among Laboratory‐Based and Clinical and Translational Researchers: The University of California, San Francisco Experience. Issue 1 (9th January 2014) - Wides, Cynthia; Mertz, Elizabeth; Lindstaedt, Bill; Brown, Jeanette
Abstract In 2005 the University of California, San Francisco (UCSF) implemented the Scientific Leadership and Management (SLM) course, a 2‐day leadership training program to assist laboratory‐based postdoctoral scholars in their transition to independent researchers managing their own research programs. In 2011, the course was expanded to clinical and translational junior faculty and fellows. The course enrollment was increased from approximate 100 to 123 participants at the same time. Based on course evaluations, the number and percent of women participants appears to have increased over time from 40% (n = 33) in 2007 to 53% (n = 58) in 2011. Course evaluations also indicated that participants found the course to be relevant and valuable in their transition to academic leadership. This paper describes the background, structure, and content of the SLM and reports on participant evaluations of the course offerings from 2007 through 2011.